Factors Predicting Sleep Quality in Sepsis Survivors: A Cross-Sectional Study - Pongsuwun, Kewalin; Puwarawuttipanit, Wimolrat; Kongkar, Ruttanaporn; Rongrungruang, Yong (Pacific Rim International Journal of Nursing Research, 2025)
Sepsis incidence is rising globally; however, advancements in sepsis management have improved survival rates. Many sepsis survivors experience poor sleep, which is associated with higher mortality and slower recovery. This cross-sectional study aimed to identify factors predicting sleep quality among sepsis survivors during hospitalization. The study included 138 sepsis survivors aged over 18 years who were admitted to the general medical ward at a super-tertiary hospital in Bangkok, Thailand. Research instruments included the Personal Information Questionnaire, Medical History Questionnaire, the Charlson Comorbidity Index, the Verran and Snyder-Halpern Sleep Scale, the Caring Professional Scale, and the Depression Anxiety Stress Scale-21. Descriptive statistics were employed to describe the characteristics of the participants, and multiple regression analysis was utilized to investigate the factors influencing sleep quality. Of the 138 sepsis survivors, 73 (52.90%) experienced poor sleep quality. Together, five predictive variables explained 47.50% of the variance in their sleep quality with statistical significance. Healthcare personnel support was the strongest predictor of sleep quality in sepsis survivors, with anxiety, comorbidities, depression, and stress following in significance. This finding highlights the importance of health care personal support. Nurses should assist sepsis survivors through psychological support, understanding, and information to reduce anxiety, depression, stress, complications, or severity of comorbidities. Addressing these problems through targeted interventions and comprehensive support strategies is crucial for enhancing their sleep quality, ultimately leading to long-term positive health outcomes.